FEATURES OF ENERGY EFFICIENT UPGRADE OF HISTORIC BUILDINGS (ILLUSTRATED WITH THE EXAMPLE OF SAINT-PETERSBURG) - Murgul, Vera (Journal of Applied Engineering Science, 2014)
In most European countries, including Russia, the requirements for building heat insulation are increasingly stringent. Historic buildings have become "energy inefficient" in terms of walling thermal upgrading aimed at reduced energy consumption. However, unlike the mass series of buildings, the historic ones are of cultural and architectural value. The energy efficient upgrade must not result in the lost of their historical authenticity. The article questions the applicability of existing standards for the thermal insulation of historic buildings, in particular, the "pros" and "cons" of walling thermal insulation. It discusses the need to preserve the exterior of the buildings that are monuments of history and culture as well as the historically-formed construction system. It puts forward the idea of improving the quality of indoor climate in residential buildings instead of energy savings at all costs.
Keywords: Heat insulation; Thermal insulation; Reconstruction; Upgrading; Historic buildings; Energy efficiency